2015
DOI: 10.3390/su70911799
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Sustainable Universities between the United States and China: Cases of Indiana University and Tsinghua University

Abstract: It is widely accepted that universities can play critical roles in promoting sustainability. In the United States and China, many universities have initiated sustainability programs. Employing Indiana University, Bloomington, the U.S. (IUB) and Tsinghua University, Beijing, China (Tsinghua) as two cases, we examine the conceptualization and implementation of university sustainability programs through a comparison of their respective definitions, goals, organizational dynamics, and strategies. We find that IUB'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 23 publications
(20 reference statements)
0
17
0
3
Order By: Relevance
“…The main cause of this disparity would be that the scores of high performing students have limited room for improvement. These data, as part of a broader set of indicators for the Education for Sustainable Development (ESD), serve to promote the comparison of student performance, monitoring, and data collection [50,51], in addition to promoting the processes of benchmarking and promoting access to OER through ICT.…”
Section: Discussionmentioning
confidence: 99%
“…The main cause of this disparity would be that the scores of high performing students have limited room for improvement. These data, as part of a broader set of indicators for the Education for Sustainable Development (ESD), serve to promote the comparison of student performance, monitoring, and data collection [50,51], in addition to promoting the processes of benchmarking and promoting access to OER through ICT.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, significantly more attention has been devoted to sustainability-specific institutional policies, for example sustainability policies or plans [14,34,35,37,38]. Typically, in SHE research strategic plans are often only briefly mentioned in a paragraph or two of a larger study [4,6,26,39].…”
Section: Strategic Planning In Higher Educationmentioning
confidence: 99%
“…These global initiatives also inspired China's sustainability development in higher education [3][4][5]. Yuan and Zuo's study of a Chinese university found that university students are aware of sustainability issues and place great importance to the social aspect of the sustainability [4].…”
Section: Introductionmentioning
confidence: 99%
“…Yuan and Zuo's study of a Chinese university found that university students are aware of sustainability issues and place great importance to the social aspect of the sustainability [4]. Zou et al carried out a comparative case study between Indiana University in US and Tsinghua University in China and found that the former emphasizes the environmental, economic, and social aspects of university sustainability equally, while the latter focuses more on the environmental aspect [5]. A local standard titled Evaluation Standard for Green Campus (ESGC) (CSUS/GBC 04-2013) as a voluntary scheme was launched in 2013.…”
Section: Introductionmentioning
confidence: 99%